Тема и Жучка: рассказ / Н. Г. Гарин-Михайловский ; худож. Д. Штеренберг - Гарин-Михайловский Николай Георгиевич (Книга за книгой, 1982)
3-4кл Экземпляры: (20200117) / Инвентарный номер: 50474 / Цена: 60.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Г 20 / ББК: 84(2Рос=Рус)1